2011
DOI: 10.2528/pierm11070502
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Source Problem: A Comparison Between the Cases of Electric and Magnetic Sources

Abstract: Abstract-This work deals with the inverse source problem starting from the knowledge of the radiated field in the near field zone. The inverse problem is stated as the inversion of a linear integral equation and the Singular Value Decomposition (SVD) is exploited as an analysis and inversion tool. In particular, here, we deal with a 2D geometry and aim at comparing the features of the inverse problem in dependence on the nature of the source (electric or magnetic).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This is because the kernel function, being far from its singularity, behaves as an entire function of exponential type [10]. Numerical studies have been already presented in literature [17,18] confirming such a behavior. What is more a heuristic formula was provided in [17] relating the critical index mentioned above to the parameters of the radiation configuration.…”
Section: Mathematical Preliminariesmentioning
confidence: 74%
See 2 more Smart Citations
“…This is because the kernel function, being far from its singularity, behaves as an entire function of exponential type [10]. Numerical studies have been already presented in literature [17,18] confirming such a behavior. What is more a heuristic formula was provided in [17] relating the critical index mentioned above to the parameters of the radiation configuration.…”
Section: Mathematical Preliminariesmentioning
confidence: 74%
“…A more interesting difference between the magnetic and the electric sources resides in the way they convey information. To be more precise, in [18] it has been numerically observed that while for the magnetic case the spatial spectral content carried out by the singular functions moves towards high frequencies as their index increases (within the relevant range ⋯ N 0, , ), for the electric source just the opposite is true. For readerʼs convenience, figure 4 shows the spectral content associated to different values of the SVD truncation index N T .…”
Section: Comparing Magnetic and Electric Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved by introducing a windowing sequences W n which multiplies the terms within the series in Eq. (2). The simplest approach is the truncated singular value decomposition (TSVD) [4] for which W n = 1 for 0 ≤ n ≤ N i and W n = 0 for n > N i , N i being the truncation index to be fixed according to "tolerable" noise level.…”
Section: Preliminaries and Notationmentioning
confidence: 99%
“…Actually, the problem setting requires defining not only the radiation operator G † but also the source and field functional spaces X and Y [1,2]. Both these spaces depend on the domains where s and f are supported.…”
Section: Introductionmentioning
confidence: 99%